PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS DIGIMONICA PADA PEMBELAJARAN PAI DAN BUDI PEKERTI KELAS VIII SMPN 13 MALANG - Lutviatul Khusna; Arief Ardiansyah; Lia Nur Atiqoh Bela Dina (VICRATINA, 2022)
Learning Media has an important role in a process learning. Along with technology, Along with the progress of the times, today there are many learning media based on computer and internet technology. However, in class VIII SMPN 13 Malang, the learning media is still rare used in the PAI learning process, as a result interest in learning and students low participation. The type of research used is research and development by adapting the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research was carried out from June, where the study sample was 32 Class students. Technique data collection used questionnaires and interviews. Experimental design used is an experimental design. One small group and big group. Data analysis using quantitative and qualitative techniques analysis.  The results of this development research are PAI and Budi Pekerti learning media based on digimonica which is applied in PAI learning for class VIII SMPN 13 Unlucky. At the product validation stage, the results of the validation with media experts get a score of 97%, material validation gets a score of 73%, while validation learning experts got a score of 68%.  can be concluded that The product developed has a feasibility level in the Digimonica media.